Construction of Virtual Neuron and Consolidation of Sleep and Memory Process– A Molecular Docking and Biomathematical Approach - Zhao, Bin; Cao, Jinming; Huang, Kuiyun; Jiang, Xia; Tang, Jingfeng (Journal of Model Based Research, 2019)
This methods paper combines molecular docking and biomathematical modeling to construct a virtual neuron framework for studying sleep‑related memory consolidation. It outlines model components and validation approach.
Keywords: Virtual Neuron; two-stage model; SWS sleep; REM sleep; memory consolidation; sleep deprivation